The Attitudes of Teachers towards Multicultural Education - Karacabey, Mehmet Fatih; Ozdere, Mustafa; Bozkus, Kivanc (European journal of educational research, 2019)
The purpose of this study is to determine the teachers' attitudes toward multicultural education. This is a survey study and the participants of the study were 248 teachers who are teaching Turkish to the Syrian immigrants in Sanliurfa. The data for this study was collected through a 5-point Likert scale called "Teachers' Multicultural Attitude Scale". According to findings, it is determined that teachers have positive attitudes towards multicultural education. Their attitudes do not differ in a statistically significant way according to their gender, mother tongue, and professional seniority. Literature teachers were found to have more positive attitudes than class teachers. Based on the findings, it can be suggested that more research is needed on how to develop, alter teaching methods and programs according to multicultural education and why teachers of certain subjects have a more positive attitude towards multicultural education. Also, studies that investigate if teachers’ attitudes towards multicultural education affect students’ academic achievement, social adaptation processes and so on may provide useful information. The participation of teachers in cultural exchange programs, formal education, courses may be useful to raise their awareness and competency on multicultural education.